A copper-(lignin/silica/fatty acids) complex as an antioxidant/electrical conductivity agent for rubber composites (Part iii). Issue 1 (5th April 2021) - Othman, Hoda Sabry; El-Hashash, Maher A.; El-Sabbagh, S.H.; Ward, A.A.; Nawwar, Galal A.M.
Abstract : Purpose: Calcium and Zinc lignates were proven to be good antioxidants for rubber composites. The purpose of this paper is to evaluate the copper lignate antioxidant activity along with evaluating its electrical conductivity in rubber composites. Design/methodology/approach: The antioxidant activity of the Cu-LSF complex was compared with that of standard commercial antioxidant additives as a green alternative. The rheological characteristics, thermal aging and mechanical and electrical properties were evaluated for the NBR vulcanizates containing the different antioxidants in the presence or absence of coupling agents. Findings: Results revealed that the Cu-LSF complex (5 phr) can function as a compatibilizing, antioxidant and electrical conductivity agent. Originality/value: The new copper complex prepared from paper-pulping black liquor of wastes could be used as a green antioxidant and electrical conductivity agent in rubber composites.